Long run performance of Islamic debt issue: Role of the agency environment - Ibrahim, Yusnidah; Uddin, Md Mohan; Minai, Mohd Sobri (2012)
Reliance on Islamic debt securities is one of the most important features of the unique financial environment in Malaysia, also known as the largest Islamic capital market. This study measures one, two, and three year performance of Islamic debt issues using samples of 113, 101, and 86 Islamic debt issues, respectively, during the period 2001 -2009.Using linear regression, this study also attempts to uncover the agency environment related determinants of this performance. Results indicate that the long run buy and hold abnormal return in two and three year period following Islamic debt issues is positive.This study finds that growth opportunity and free cash flow significantly influence the long run performance of the Islamic debt issuer, depending on the degree of capital structure change.